The Effect of Asbestos Waste as an Additive to Concrete Mixtures - Syamsul Bahri Bahar (AIQU: Journal Multidiscipliner of Science, 2023)
The purpose of this study was to determine the material characteristics of coarse aggregate, fine aggregate and asbestos waste and to determine the strength value of concrete. The choice of using concrete construction takes into account the availability of materials in the area, the price is relatively cheap, has strength and is resistant to environmental conditions. In the current technological era, mixing materials to make a concrete structure can be done by looking for substitute materials or additional materials to produce a strong and resistant concrete mix by utilizing waste materials found in the surrounding environment. One of the wastes that can be utilized is asbestos waste, this is because there are quite a lot of asbestos wastes available and there are several waste storage areas. To produce good concrete, a concrete strength test must be carried out so that it produces the desired material in accordance with the Indonesian National Standard (SNI). The results showed that the material characteristics of the sand were black and 0.55–2.5 mm in size, tended to have poor adhesion and high chloride content, while the characteristics of crushed stone varied in size and high hardness. and black and gray, the compressive strength test of asbestos added concrete for 3 days was 42.2 kg/cm2, 7 days 62.1 kg/cm2 and 28 days 75.5 kg/cm2.